AMR in low-resource settings: Médecins Sans Frontières bridges surveillance gaps by developing a turnkey solution, the Mini-Lab. (October 2021) - Ronat, Jean-Baptiste; Natale, Alessandra; Kesteman, Thomas; Andremont, Antoine; Elamin, Wael; Hardy, Liselotte; Kanapathipillai, Rupa; Michel, Justine; Langendorf, Céline; Vandenberg, Olivier; Naas, Thierry; Kouassi, Felix
Abstract: Background: In low- and middle-income countries (LMICs), data related to antimicrobial resistance (AMR) are often inconsistently collected. Humanitarian, private and non-governmental medical organizations (NGOs), working with or in parallel to public medical systems, are sometimes present in these contexts. Yet, what is the role of NGOs in the fight against AMR, and how can they contribute to AMR data collection in contexts where reporting is scarce? How can context-adapted, high-quality clinical bacteriology be implemented in remote, challenging and underserved areas of the world? Objectives: The aim was to provide an overview of AMR data collection challenges in LMICs and describe one initiative, the Mini-Lab project developed by Médecins Sans Frontières (MSF), that attempts to partially address them. Sources: We conducted a literature review using PubMed and Google scholar databases to identify peer-reviewed research and grey literature from publicly available reports and websites. Content: We address the necessity of and difficulties related to obtaining AMR data in LMICs, as well as the role that actors outside of public medical systems can play in the collection of this information. We then describe how the Mini-Lab can provide simplified bacteriological diagnosis and AMR surveillance in challenging settings. Implications: NGOs are responsible for a large amount of healthcare provision in some very low-resourced contexts. As a result, they also have a role in AMR control, including bacteriological diagnosis and the collection of AMR-related data. Actors outside the public medical system can actively contribute to implementing and adapting clinical bacteriology in LMICs and can help improve AMR surveillance and data collection.